STEREOTIP TERHADAP MUSLIM DALAM FILM BULAN TERBELAH DI LANGIT AMERIKA - Santoso, Fitriani Dyah; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2019)
ABSTRACT The emergence of negative stereotypes about Islam was formed and built by the mass media through the messages it brought, especially after the tragedy of the World Trade Center on September 11, 2001. One type of mass media is film. As a message conveyor, film has a rather strong effect because it is usually based and inspired from the reality that exists in real life The film that shows American stereotypes of Muslim is the film Bulan Terbelah di Langit Amerika. This type of research is descriptive-qualitative. Data collection techniques using the study of visual material by examining various signs both verbal and non verbal and then describe it using the semiotics theory of Roland Barthes. The results of this research shows that there are stereotypes of Muslim that are identically with terrorist, the American Islamophobia against Muslim, and then there are discrimination against Muslims. Keyword: Muslim, Representation, Semiotics, Stereotype